THE INFLUENCE OF ENTREPRENEURIAL KNOWLEDGE, SELF EFFICACY AND ENTREPRENEURIAL CHARACTER ON ENTREPRENEURIAL INTEREST OF CLASS XII STUDENTS OF SMKN 7 PANDEGLANG - Muhamad Hendi; Anandha Yhuto WP; Haris Abizar (Department of Mechanical Engineering Education, 2025)
This study aims to influence entrepreneurial knowledge, self-efficacy and entrepreneurial character simultaneously and partially on the entrepreneurial interest of class XII students of SMKN 7 Pandeglang. This study uses a survey type with a quantitative approach. Data analysis techniques in this study used Descriptive Analysis, Validity Test, Reliability Test, Analysis Prerequisite Test, Multiple Linear Regression Analysis, T Test, F Test and Determination Coefficient Analysis Test (R2). The sample used in this study was 75 students. The results of the study with the t test showed that entrepreneurial knowledge had a positive and significant effect on entrepreneurial interest, self-efficacy had a positive and significant effect on entrepreneurial interest, entrepreneurial character had a positive and significant effect on entrepreneurial interest and simultaneously (f test) there was a positive and significant effect of entrepreneurial knowledge, self-efficacy, and entrepreneurial character on Entrepreneurial Interest. This is evidenced by the results of the F test which showed a calculated F value of 22.756 and a significance of 0.000, where sig F <0.05. The coefficient of determination (R²) is 0.490, which means that 49.0% of students' interest in entrepreneurship can be explained by the variables of entrepreneurial knowledge, self-efficacy, and entrepreneurial character. While the remaining 51.0% is influenced by other variables that were not analyzed in this study.